Time-of-Flight Neutron Diffraction (TOF-ND) Analyses of the Composition and Minting of Ancient Judaean “Biblical” Coins - Stephen E. Nagler; Alexandru D. Stoica; Grigoreta M. Stoica; Ke An; Harley D. Skorpenske; Orlando Rios; David B. Hendin; Nathan W. Bower (Journal of Analytical Methods in Chemistry)
TOF-ND elastic scattering of thermal neutrons offers some important advantages over X-ray diffraction (XRD), X-ray fluorescence (XRF), and metallography for the study of archaeological and numismatic problems. Traditional analytical methods are usually destructive and often probe only the surface. Neutrons deeply penetrate samples, simultaneously giving nondestructive bulk information about the crystal structure, composition, and texture (alignment of crystallites) from which thermomechanical manufacturing processes (e.g., cast, struck, or rolled) may be inferred. An analysis of the metal composition and minting processes used for making ancient Judaean bronze and leaded bronze coins from first century BCE and CE is used as a case study. One of the first ND analyses of the temperature used for striking bronze coins is also presented.